Nopol-Based Quinoline Derivatives as Antiplasmodial Agents - Nyamwihura, Rogers J. (Molecules, 2021)
Malaria remains a significant cause of morbidity and mortality in Sub-Saharan Africa and South Asia. While clinical antimalarials are efficacious when administered according to local guidelines, resistance to every class of antimalarials is a persistent problem. There is a constant need for new antimalarial therapeutics that complement parasite control strategies to combat malaria, especially in the tropics. In this work, nopol-based quinoline derivatives were investigated for their inhibitory activity against Plasmodium falciparum, one of the parasites that cause malaria. The nopyl-quinolin-8-yl amides (2–4) were moderately active against the asexual blood stage of chloroquine-sensitive strain Pf3D7 but inactive against chloroquine-resistant strains PfK1 and PfNF54. The nopyl-quinolin-4-yl amides and nopyl-quinolin-4-yl-acetates analogs were generally less active on all three strains. Interesting, the presence of a chloro substituent at C7 of the quinoline ring of amide 8 resulted in sub-micromolar EC(50) in the PfK1 strain. However, 8 was more than two orders of magnitude less active against Pf3D7 and PfNF54. Overall, the nopyl-quinolin-8-yl amides appear to share similar antimalarial profile (asexual blood-stage) with previously reported 8-aminoquinolines like primaquine. Future work will focus on investigating the moderately active and selective nopyl-quinolin-8-yl amides on the gametocyte or liver stages of Plasmodium falciparum and Plasmodium vivax.